MODERN LEARNING FROM ENGLISH WEB DIDACTIC PRINCIPLES OF PLATFORM DEVELOPMENT - Ergashev Nuriddin G‘ayratovich; Pulatova Dilafruz daughter of Yakub (American Journals, 2024)
The process of using the web platform on the basis of informatization of education increases the level of activity of the learner, grows alternative thinking skills, forms the skill of seeking solutions to the tasks set, allows you to develop the skills of computer modeling, algorithmic construction and programming of the objects and phenomena under study, and integrate the results of interaction between them.
Keywords: English, web platform, modern educational web platforms, didactic principles, informatization of education, competency of information.